1991
DOI: 10.1088/0022-3727/24/3/014
|View full text |Cite
|
Sign up to set email alerts
|

Current transfer between two parallel electrical arcs

Abstract: A fast backward-jump type arc motion is observed with an arc running on rails. It is shown by the use of conductivity probes that this motion does not correspond to a continuous displacement of an ionized high-temperature region. The model of current transfer between two parallel arcs is adopted to explain the jump motion, for which a high rising speed of the arc voltage is a decisive factor. The current transfer is considered to be different from the re-ignition of a post-arc current.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…The probes being placed at y = 7 mm away from the plane in which the arc evolves, such inversions can be observed only when both arcs are more than 20 mm apart (figure 10). Such behaviour was explained with the model of current transfer developed by Haug [3]. He observed no increase of conduction in the electrode gap during a re-striking, which seemed to prove that there was no arc.…”
Section: Study Of the Re-strikingmentioning
confidence: 79%
“…The probes being placed at y = 7 mm away from the plane in which the arc evolves, such inversions can be observed only when both arcs are more than 20 mm apart (figure 10). Such behaviour was explained with the model of current transfer developed by Haug [3]. He observed no increase of conduction in the electrode gap during a re-striking, which seemed to prove that there was no arc.…”
Section: Study Of the Re-strikingmentioning
confidence: 79%
“…The conductance-probe measurement is the most widespread technique to demonstrate that a medium is still conductive [2,3,12]. However, deriving a gas temperature from it is difficult.…”
Section: Arc Re-strike Mechanismmentioning
confidence: 99%
“…The important values of the electric field explain that the arc always re-strikes between the bottom of the splitting plate and one of the electrodes. In fact, Haug et al showed that re-strikes are more frequent when the distance between electrodes is small [12]. Moreover, note that re-strikes take place during the decreasing phase of the current.…”
Section: Re-strike Characterizationmentioning
confidence: 99%